Five new species and key for Australian Epyris Westwood (Hymenoptera, Bethylidae) - Tribull, Carly Melissa (Zootaxa, 2016)
Epyris Westwood, 1832 is the largest genus within Bethylidae, but few species are known from Australia, with only two species described. Following trips undertaken by the author to sort material from the Canadian National Collections, Queensland Museum, and Australian National Insect Collection, the number of described species is expanded to seven with the addition of E. loisae Tribull, sp. nov., E. herschae Tribull, sp. nov., E. carpenteri Tribull, sp. nov., E. azevedoi Tribull, sp. nov., and E. fulgeocauda Tribull, sp. nov. Descriptions and illustrations of each new species are provided, as well as a key to the known Australian Epyris species.